Functional gastrointestinal disorders in schoolchildren with chronic abdominal pain in a pediatric digestive endoscopy unit - Velasco-Benítez, Carlos Alberto; Calderón-Guerrero, Otto Gerardo; Ramírez-Villamizar, Johanna (Universidad y Salud, 2019)
Introduction: The indication of an upper digestive tract endoscopy (UDTE) in children with chronic abdominal pain (CAP) has little evidence. However, this test continues to be requested in children with functional gastrointestinal disorders (FGIDs). Objective: To determine the prevalence and possible associations of FGIDs in children of a Pediatric Digestive Endoscopy Unit using the Rome III Criteria. Materials and methods: A prevalence study of 37 schoolchildren. Sociodemographic, anthropometric and clinical variables were assessed. The statistical analysis included estimation of the proportion of children with FGIDs and its corresponding 95% CI. Other assessments included estimation of percentages, averages, standard deviations, ranges, univariate analysis, possible occurrence of associations between the variable, and a two-tailed Fisher’s exact test with a significance set at p<0.05. Results: The mean age of child participants was 11.3±2.1 years and 62.2% of them were female. The prevalence of FGIDs was 73%, more than half of them presenting functional abdominal pain (FAP) and irritable bowel syndrome (IBS). There were no significant differences in terms of sociodemographic, anthropometric and clinical variables. Conclusions: The prevalence of FGIDs is high in children with CAP who undergo UDTE as part of the study of this disorder, being FAP and IBS the most frequent.